2006
DOI: 10.1185/030079906x132532
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the total costs of blood delivery to hospital oncology and haematology patients

Abstract: This study estimates the cost of an average blood transfusion of 2 units to be 546.12 pounds sterling. It should be noted that significant indirect costs, such as those incurred by patients, their carers and societal costs, have not been considered. Against the background of finite blood resources and other factors such as patient quality of life, blood transfusion may not represent the best choice for patient care. Alternative treatments should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…This ambitious and informative project had a not unexpected outcome; the results show that the cost of transfusion for surgical procedures is higher than previously reported and that the acquisition cost of red blood cells (RBCs) from blood banks is a relatively small contributor to hospitals' total transfusion cost, representing less than one‐third of the cost for each of the four hospitals. Other researchers have reported similar higher than previously reported costs for transfusion of intensive care unit (ICU) patients 14 …”
supporting
confidence: 67%
“…This ambitious and informative project had a not unexpected outcome; the results show that the cost of transfusion for surgical procedures is higher than previously reported and that the acquisition cost of red blood cells (RBCs) from blood banks is a relatively small contributor to hospitals' total transfusion cost, representing less than one‐third of the cost for each of the four hospitals. Other researchers have reported similar higher than previously reported costs for transfusion of intensive care unit (ICU) patients 14 …”
supporting
confidence: 67%
“…Studies from European countries, the USA and Canada have shown that cost of overhead, disposables and labour for testing and administration clearly ad to acquisition cost of the BCs. In a study conducted in 2006, Agrawal et al give an estimate of €770 (U526) for the transfusion of two units of RBC from the perspective of the hospital provider in the UK with about 50% of the total cost being attributable to the acquisition cost of the two RBC units [24]. Other studies have led to similar results [6,25].…”
Section: Transfusion Practicementioning
confidence: 83%
“…52,56,58,60 The index year for pricing was 2011/12 and prices from earlier (or later) years were inflated (or deflated) to 2011/12 values using the hospital and community hospital services (HCHS) pay and prices index. 53,55 Stickers giving the product codes for the knee prosthesis components used in primary knee replacement and revisions were attached to the surgeon's form to indicate which brand and model was used in that operation.…”
Section: Analysis Lmentioning
confidence: 99%